1987
DOI: 10.2320/matertrans1960.28.32
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Temperature Embrittlement of Dispersion Hardened Cu&ndash;GeO<SUB>2</SUB> Polycrystals

Abstract: In order to clarify the mechanism of the so-called intermediate temperature embrittlement, CuGeO2 dispersion-hardened alloys were tensile tested at various temperatures between room temperature and 900 K with the strain rate of 10-3 s-1 or 10-4S-1. In the case of single crystals, elongation to fracture increased monotonically with increase in temperature. On the other hand, the ductility of polycrystals first decreased and then increased again, showing the ductility minimum associated with intergranular fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…On the other hand, particles also act as preferential sites for the nucleation of voids because they concentrate stress in their neighbourhood 153,155,156,161 . Finite-element calculations in Ref.…”
Section: Multiphase Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, particles also act as preferential sites for the nucleation of voids because they concentrate stress in their neighbourhood 153,155,156,161 . Finite-element calculations in Ref.…”
Section: Multiphase Alloysmentioning
confidence: 99%
“…10 illustrates this for internally oxidised Cu-Al 6 . This, in turn, will lower T E if it is defined as that temperature where the ductility falls below a given value 153,156 .…”
Section: Multiphase Alloysmentioning
confidence: 99%
“…Onaka et al 1 attributed the loss of ductility in dispersion-hardened alloys to the stress concentration at grain-boundary particles and the occurrence of grainboundary fracture. Onaka et al 1 attributed the loss of ductility in dispersion-hardened alloys to the stress concentration at grain-boundary particles and the occurrence of grainboundary fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Onaka et al 1 attributed the recovery of ductility at higher temperatures to the occurrence of dynamic recrystallization near grain boundaries, since dynamic recrystallization would relieve the stress-concentration induced by GBS. In this study, dynamic recrystallization was observed only in Cu-0.41SiO 2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation